Evaluation process radiological in ternopil region method of box models - Матвєєва, І.В.; Кутлахмедов, Ю.О.; Ісаєнко, В.М.; Криворотько, В.М. (Proceedings of National Aviation University, 2006)
Results of radionuclides Sr-90 flows analyses in the ecosystem of Kotsubinchiky village of Ternopolskaya oblast were analyzed. The block-scheme of ecosystem and its mathematical model using the box models method were made. It allowed us to evaluate the ways of dose’s loadings formation of internal irradiation for miscellaneous population groups – working people, retirees, children, and also to prognose the dynamic of these loadings during the years after the Chernobyl accident.